THE IMPLEMENTATION OF PRAGMATIC STRATEGIES IN THE TRANSLATION OF THE TALES OF THE THREE BROTHERS - Adani Nur Sabrina (Jurnal Sosial Humaniora dan Pendidikan, 2024)
This study examined the implementation of Chesterman’s pragmatic strategies in the Indonesian translation of The Tales of the Three Brothers from The Tales of Beedle the Bard. Chesterman’s theory includes 10 pragmatic strategies: cultural filtering, explicitness change, information change, interpersonal change, illocutionary change, coherence change, partial translation, visibility change, transediting, and other pragmatic changes. This research employed a qualitative descriptive method to analyse the strategies applied in the translation. The findings revealed 14 occurrences of three pragmatic strategies. Explicitness change emerged as the most dominant strategy with 11 data, divided into six implicitations and five explicitations. Meanwhile, two data were found from the information change strategy and one data from interpersonal change. This research is hoped to contribute to the field of translation by offering a practical application of Chesterman’s theory to literary translation.